Investigating The Challenges Of Implementing Peer Feedback To Enhance Efl Students’ Writing Accuracy - Djafri, Leila; Benmadani, Sara (El Omda in Linguistics and Discourse Analysis, 2023)
Improving students’ written performance has long been a challenging task for students and teachers alike. The current study aims at investigating the challenges facing the implementation of peer feedback as an instructional pedagogy to enhance students’ writing accuracy. To carry out this study, a mixed-methods approach to data collection and analysis was applied wherein an online questionnaire was administered to EFL students in addition to an interview conducted with teachers in charge of the written expression module at the Department of English at M’sila University. The results obtained revealed that peer feedback is not implemented in writing instruction. Hence, training students on how to give and receive peer feedback is recommended.